(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: the aim is to compare the performance in psycholinguistic abilities of students of Venezuelan and Colombian nationality frontier inhabitants of two public educational institutions. METHODS: longitudinal descriptive study with analysis of multiple correspondence by cluster when applying the ILLINOIS test of psycholinguistic abilities in its third version. RESULTS: average perfor-mance is evidenced in the population participating in the linguistic compound, the oral language of foreign students is better, while in students of natural origin they perform in written language. ANAL-YSIS AND DISCUSSION: the performance in psycholinguistic skills evaluated has shown homoge-neity in the sample studied, this is attributed to the number of students assessed and contrasts the available literature that has shown inferior performance in foreign students. CONCLUSIONS: it is important to increase the size of the sample to confirm the findings obtained